International Normalized Ratio Relevance to the Observed Coagulation Abnormalities in Warfarin Treatment and Disseminated Intravascular Coagulation - Walborn, Amanda; Williams, Mark; Fareed, Jawed; Hoppensteadt, Debra (Clinical and applied thrombosis/hemostasis, 2018)
The development of coagulation abnormalities is common in patients with sepsis. Sepsis-associated coagulopathy (SAC) is typically diagnosed by prothrombin time (PT) prolongation or elevated international normalized ratio (INR) in conjunction with reduced platelet count. INR is also used to monitor warfarin-treated patients. However, due to the different natures of SAC and warfarin anticoagulation, it is likely that the same INR value provides different information in these two patient populations. The purpose of this study was to compare measures of coagulation function and clotting factor levels in patients with SAC to those observed in patients receiving warfarin anticoagulation. Deidentified plasma samples were collected at baseline from patients diagnosed with SAC and from patients receiving warfarin. These plasma samples were evaluated for PT/INR, activated partial thromboplastin time (aPTT), fibrinogen, and functional and immunologic levels of factors VII, IX, and X. Both aPTT and fibrinogen correlated with INR in patients with SAC, but not in patients treated with warfarin. Factors VII, IX, and X showed an inverse relationship with INR in the anticoagulated patients; however, no relationship between factor level and INR was observed in patients with SAC. Distinct patterns of coagulopathy were observed in patients with SAC and patients receiving warfarin anticoagulation, and equivalent INR values were associated with distinct coagulation profiles in the two patient groups. These results suggest that an abnormal INR provides different information about the coagulation status in patients with disseminated intravascular coagulation than in patients receiving warfarin. This may indicate that an equivalently increased INR predicts different bleeding risks in these two patient groups.